S122 Effects of vaped e-cigarette liquid condensate upon human alveolar macrophage function. to vape or not to vape that is the question?. (15th November 2016) - Scott, A; Lugg, ST; D'Souza, V; Lewis, K; Dosanjh, D; Naidu, B; Thickett, DR
Abstract : Introduction and objectives: Electronic cigarette usage or "vaping" has risen exponentially in recent years in smokers and ex-smokers. Published data suggests that vaping e-cigarette liquid (ECL) may not be as benign as propounded by e-cigarette companies which are increasingly owned by "big tobacco". Much of the current literature has focused on the effect of non-vaporised ECL – such studies do not fully reflect the exposure of the user, as the process of vaping causes chemical changes in ECL. To investigate the effect of unvaped ECL and vaped e-cig condensate (ECVC) using our novel system, with and without nicotine, on alveolar macrophage (AM) viability and immune responses. Methods: We developed a novel method to produce ECVC to allow direct comparison with unvaped ECL. Nicotine concentration as assessed by GFID was 31 mg/ml in ECL and 26 mg/ml in ECVC. AMs were obtained from lung resection tissue and treated with ECVC/ECL ± nicotine. Cell viability was assessed by cell titre aqueous assay, apoptosis, necrosis and markers of macrophage phenotype (CD68, CD80, CD163, CD206) were assessed by flow cytometry. IL-8 release by AMs was assessed by ELISA. Results: AM culture with ECL or ECVC resulted in dose dependent reduction in cell viability. ECVC was cytotoxic at lower concentrations than ECL (0.8% ECVC vs 5 %ECL, n = 6). 24 hour culture with 1% ECVC resulted in a 5fold increase in AM apoptosis and 2 fold increase in necrosis compared with 1%ECL (p = 0.079, n = 5). Nicotine containing ECVC caused more apoptosis vs nicotine free ECVC (27.2% vs 13.4%, (p = 0.0079, n = 4). Culture with 0.6%ECVC significantly increased supernatant levels of IL-8 compared with 1% ECL (p = 0.015, n = 4). ECVC was also found to affect macrophage phenotype, showing both nicotine dependent/independent regulations of markers of macrophage m1/m2 polarisation (CD80 p = 0.0357, CD163 p = 0.0179, CD206 p = 0.0357, n = 6). Conclusions: Our novel system creates ECVC which is sterile, minimises loss of nicotine and prevents dilution of the vapour. Vaped E-cigarette condensate is significantly more toxic to AMs than non-vaped e cigarette liquid. Furthermore, ECVC with nicotine is significantly more toxic than ECVC without Nicotine. Effects shown on inflammatory cytokine production and markers of macrophage polarisation indicate both nicotine dependent and independent effects of ECVC on alveolar macrophages.